Structural phase stability and intrinsic magnetic properties of SmFe11Ti with interstitial B, N and C atoms - D. Sodkhuu; N. Tsogbadrakh; N. Jargalan; D. Odkhuu (AIP Advances)
ThMn12-ordered SmFe11Ti alloy has potential for high-performance permanent magnets due to its desirable hard magnetic feature and high Curie temperature. Employing full-potential density functional theory calculations, we investigate structural and intrinsic magnetic properties of SmFe11TiZx (Z = B, N, and C; x = 0, 0.5, and 1) alloys. It is predicted that the presence of interstitial N atoms can improve saturation magnetization μ0Ms up to 1.3 T for SmFe11TiN while uniaxial magnetocrystalline anisotropy Ku can be elevated up to 12.5 MJ/m3 for SmFe11TiB. These values are higher than the corresponding values of 1.2 T and 7.2 MJ/m3 of SmFe11Ti phase. The underlying mechanism is the interplay between the interstitial doping induced volume expansion and modification in the strong spin-orbit coupled Sm 4f electron energy levels. The present computational study suggests that the interstitial doping with 2p-electron elements would be a viable route for improving phase stability and intrinsic permanent magnetic properties in ThMn12-type structures.